Training in Late Careers: A Structural Approach - Teresa Backhaus (Institute of Labor Economics (IZA), 2023)
This study investigates the role of on-the-job training in the employment outcomes of less educated men in their late careers. Using survey data from the German National Education Panel Study adult cohort, I estimate a structural dynamic discrete-choice model reflecting the trade-offs of the employees' training participation decision. The data set enables me to distinguish whether non-participation is due to lack of availability of training or due to individual cost-benefit considerations. As a consequence, I can investigate whether future policy interventions should target the provision of training or the individual participation incentives. I find that on-the-job training has a positive impact on the employees' employment prospects. Counterfactual simulations show that a reduction of the individual training costs would increase training participation and positively affect the employment rate near retirement. In contrast, an increase in the general availability of training would not be effective.
Keywords: E24; J14; J22; J24; M53; 330; on-the-job training; late career; less educated; structural model